Long term electroencephalography in preterm neonates: Safety and quality of electrode types. Issue 7 (July 2018) - El Ters, Nathalie M.; Mathur, Amit M.; Jain, Siddharth; Vesoulis, Zachary A.; Zempel, John M.
Highlights: Hydrogel and gold cup electrodes can be used safely in long-term EEG studies in preterm neonates. Hydrogel electrodes are non-inferior to gold cup electrodes in terms of replacement frequency and recording quality. Hydrogel electrodes showed a longer uninterrupted recording time than gold cup electrodes. Abstract: Objectives: The objective of this study was to compare gold cup and hydrogel electrodes for frequency of electrode replacement, longevity of the original electrodes after initial placement, recording quality, and skin safety issues in long-term EEG studies in preterm neonates. Methods: We performed a prospective trial with newborns born at ≥23 weeks and ≤30 weeks of gestational age (GA). Two mirror image EEG electrode arrays were utilized on consecutive subjects, where gold cup electrodes alternated with hydrogel electrodes. Results: Our sample included 50 neonates with mean GA of 27 (±1) weeks. The mean recording time was 84 (±15) hours. No difference was present in the frequency of replacement of either type across the total recording time ( p  = 0.8). We collected the time at which electrodes were first replaced, and found that hydrogel electrodes showed a longer uninterrupted recording time of 28(±2) hours vs. 20(±2) hours for gold cup electrodes ( p  = 0.01). Recording quality was similar in either type ( p  = 0.2). None of the patients experienced significant skin irritation from a discrete electrode. Conclusion: Long-term EEG studies can be performed with either gold cup or hydrogel electrodes, validating the safety and quality of both electrode types. Significance: Hydrogel electrodes are a reasonable alternative for use in long-term EEG studies in preterm neonates.